Regulation and Innovation Revisited: How Restrictive Environments Can Promote Destabilizing New Technologies - Park, Michael; Wu, Shuping; Funk, Russell J. (Organization Science, 2025)
Previous literature offers conflicting findings on how the restrictiveness of the regulatory environment—the amount of rules that prohibit specific activities—affects innovation of firms. One camp suggests that restrictiveness circumscribes the range of available technological components and therefore decreases innovation. The other camp believes that restrictiveness can lead firms to seek new alternative technological components, which could increase innovation. In this article, we develop a new theory on regulation and innovation to reconcile these views, which we test using novel data on federal regulations and the patents of 1,242 firms, from 1994 to 2013. We find that restrictiveness can have both a negative and positive relationship with innovation output depending on the level of regulatory uncertainty and the innovation type in question. Funding: This work was supported by the Mercatus Center, George Mason University, and the Strategy Research Foundation [Grant SRF-2021-DRG-8365]. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2022.16770 .